Evaluation of the Immunogenicity of a Vascular Graft Covered with Collagen Derived from the European Carp (Cyprinus carpio) and Bovine Collagen - Lambert, Lukas; Novakova, Michaela; Lukac, Peter; Cechova, Dana; Sukenikova, Lenka; Hrdy, Jiri; Mlcek, Mikulas; Chlup, Hynek; Suchy, Tomas; Grus, Tomas (BioMed research international, 2019)
Aim: To assess the systemic and local immunological response to subcutaneous implants of a vascular graft covered with collagen extracted from the European carp (freshwater fish) or with collagen of bovine origin. Methods: Pieces of a vascular graft covered by pure bovine (Bos taurus, BOV, n=14) or carp (Cyprinus carpio, CYP, n=14) collagen 5 mm in size were implanted subcutaneously in the dorsum of a Balb/cOla mice. A sham operation group of 12 animals served as the control. At 7 and 14 days after the operation, one-half of each group was terminated and blood for serum, spleen, and implant with surrounding tissue were collected. Mean cytokine (TNF-α, IL-10, IL-4, IL-1β, IL-13, and IFN-γ) levels in serum were determined using ELISA. Spleen cell cultures were used for in vitro testing of lymphocyte proliferation and cytokine secretion. Local expressions of IL-6, IL-10, TNF-α, TGF-β, CCL-2, and CCL-3 were determined using PCR. Results: We found no significant difference among control, BOV, and CYP groups in mean cytokine serum levels at seven days. At day 14, the BOV group had higher levels of TNF-α (P=.018) and both the BOV and CYP groups had lower levels of IL-4 (P=.011 and P=.047, respectively) compared with the control group. Both tested implants showed only a minimal effect on the production of selected cytokines. Cell proliferation in the CYP group stimulated by CYP gel at 14 days was significantly lower than by BOV gel in BOV group (P=.0031) or by CYP gel in the control group (P=.041). The difference between the groups in the local RNA expression of all the tested mediators both at 7 and at 14 days was not significant apart from a lower level of TNF-α in the BOV group compared to CYP at 14 days (P=.013). Conclusions: Implants covered with carp collagen induce an immunological response that is comparable to that of bovine collagen covered implants in a mouse model.
Keywords: Cattle; cévní protézy; RNA, Messenger; slezina; buněčné mikroprostředí; Cell Proliferation; skot; cytokiny; myši inbrední BALB C; kapři; kolagen; Cellular Microenvironment; Mice, Inbred BALB C; Spleen; Blood Vessel Prosthesis; Animals; zvířata; Collagen; Carps; proliferace buněk; Cytokines; messenger RNA